2014
DOI: 10.18632/oncotarget.2288
|View full text |Cite
|
Sign up to set email alerts
|

CLDN3 inhibits cancer aggressiveness via Wnt-EMT signaling and is a potential prognostic biomarker for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common fatal malignancies but the molecular genetic basis of this disease remains unclear. By using genome-wide methylation profiling analysis, we identified CLDN3 as an epigenetically regulated gene in cancer. Here, we investigated its function and clinical relevance in human HCC. CLDN3 downregulation occurred in 87/114 (76.3%) of primary HCCs, where it was correlated significantly with shorter survival of HCC patients (P=0.021). Moreover, multivariate cycloox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…Many studies have shown different expression levels of the individual CLDNs and OCLN and CLDN1 are being investigated as biomarkers for liver disease progression 103 122 147–151. From these studies, it appears that the expression of CLDNs is associated with more severe disease and/or bad prognosis in patients with HCC (table 2): epigenetic silencing of CLDN14 was significantly associated with advanced tumour state and tumour aggressiveness152; CLDN11 downregulation by miR-99 has been associated with metastasis of HCC153; and CLDN3 downregulation has been suggested to promote EMT via Wnt-β-catenin signalling 154. However, more data are needed to decipher the role of these TJ proteins in the pathogenesis of HCC.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 99%
“…Many studies have shown different expression levels of the individual CLDNs and OCLN and CLDN1 are being investigated as biomarkers for liver disease progression 103 122 147–151. From these studies, it appears that the expression of CLDNs is associated with more severe disease and/or bad prognosis in patients with HCC (table 2): epigenetic silencing of CLDN14 was significantly associated with advanced tumour state and tumour aggressiveness152; CLDN11 downregulation by miR-99 has been associated with metastasis of HCC153; and CLDN3 downregulation has been suggested to promote EMT via Wnt-β-catenin signalling 154. However, more data are needed to decipher the role of these TJ proteins in the pathogenesis of HCC.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 99%
“…In this regard, recent studies have demonstrated novel protein-protein interactions involving claudin proteins including with proteins expressed in lateral and basal domains of the cells, and its influence on cellular signaling cascade/s. Moreover, genetic changes in claudin proteins, in vitro and in vivo, are now demonstrated to modulate multitude of cellular functions including cell proliferation, migration, and by altering key signaling processes including the Notch signaling, the Wnt/β-catenin signaling, and JAK/STAT-3 signaling [26, 39, 47, 48]. …”
Section: Introductionmentioning
confidence: 99%
“…However, these associations are not always linear and highly increased expression of claudin-3 and −4 in prostate and ovarian cancers, in correlation with cancer aggressiveness, is reported [57]. Interestingly, tumor suppressor role of claudins-3 and −4 has been also reported [26, 35]. They affect the E-cadherin expression and suppress β-catenin signaling, increase in vitro cell migration, invasion, and corresponding metastasis in vivo [26, 55, 56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear β-catenin accumulation in the invasive fronts of primary tumors has been shown to lead to increased tumor metastasis [19,20]. Molecules targeting Wnt/β-catenin signaling can significantly inhibit tumor growth and EMT in many cancer types [21,22]. MSX1 is a homeobox transcription factor that plays important roles in craniofacial [23] and cardiac [24] development.…”
Section: Introductionmentioning
confidence: 99%